Combining ability studies in wheat (Triticum aestivum L.) for genetic improvement under salt stress - Kulshreshtha, Neeraj; Singh, K N (Journal of Cereal Research, 2011)
Combining ability, heritability and gene action estimates for yield and yield attributes under saline (ECiw: 15 dS/m) and normal irrigated conditions were studied using 8x8 diallel crosses in wheat. Both additive and non-additive gene action were found important in the inheritance of yield and yield attributes under normal as well as saline irrigation conditions. Under normal conditions all the traits were found to be governed by non additive gene action with low heritability, whereas under salt stress, plant height and spikelets/spike exhibited high heritability with importance of additive effects. All other traits under salt stress exhibited medium to low heritability with non-additive gene action. The genotypes Kharchia 65, KRL 19, HD 2189 and KRL 129-1 exhibited high gca and per se performance for grain yield/plant under salt stress. The crosses UP 2338/Kharchia 65 and Kharchia 65/KRL 129-1 were found to be the best combinations under salt stress for grain yield/plant.